PERKAWINAN ANAK DI DESA BULUREJO KABUPATEN BANYUWANGI (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research focuses on the processes and agents of socialization in child marriage in Bulurejo Village, Banyuwangi Regency. The purpose of this research is to explain and analyze the socialization process for the people of Bulurejo Village, Banyuwangi Regency regarding child marriage. This research uses descriptive qualitative research methods and uses the socialization theory put forward by Charles Horton Cooley and George Herbert Mead. The results of this study explain that regarding the increase in child marriage in Bulurejo Village, the increase in this case was due to changes in Law Number 16 of 2019 regarding the minimum age for marriage which increased requests for dispensation to marry by several hundred percent, this increase was driven by the most factors of child marriage in Bulurejo Village namely pre-marital pregnancy and the desire of parents to prevent their children from committing adultery. Instilling children's values ??and norms through socialization agents Cooley and Mead's socialization process is closely related to the formation of children's mindset regarding child marriage in Bulurejo Village, especially the transfer of values ??from family socialization agents. Keywords: Agent of Socialization, Child marriage, Instilling Values, Socialization Process, Instilling Values